Clinical Response of EMLA Cream in Decreasing Peripheral Cannulation Pain in Children - Tariq, Sana; Khan, Rao Ali Shan; Shahid, Arooj; Tariq, Hassan; Khan, Tanveer Ahmed; Khalique, Ahmed Bilal (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the clinical response of EMLA cream (Eutectic Mixture of Local Anaesthetics; 2.5% Lidocaine/2.5% Prilocaine) in decreasing peripheral cannulation pain in children. Study Design: Quasi-experimental study. Place and Duration of Study: Combined Military Hospital, Rawalpindi Pakistan, from May to Aug 2021. Methodology: This study was conducted on 80 paediatric patients who were classified as American Society of Anesthesiologists (ASA) Grades I and II and selected using non- probability consecutive sample. They underwent peripheral cannulation to maintain intravascular access for surgical procedure. The forty children in EMLA Group (Group-A) were applied 2.5 ml EMLA cream for 60 min, covered by Tegaderm® over suitable vein, while the 40 children in Control Group (Group-B) received no local anesthetic cream. Participants rated pain during venipuncture on Visual Analog Scale (VAS 0–10; 0, no pain; 10, intolerable pain). Results: Out of 80 patients equally divided into two groups, 40(50%) were males, while 40(50%) were females. The patients included in our study had mean age of 7.35±1.5 years. In EMLA group the mean score of pain was 1.5±0.87 compared to the Control group (mean score = 7.4±1.4; p=0.001). Conclusion: The result of our study suggests that EMLA cream is more efficacious in decreasing venipuncture pain than if no local anaesthetic cream is applied.